BUBBLES, CRASHES, AND ENDOGENOUS UNCERTAINTY IN LINKED ASSET AND PRODUCT MARKETS - Jaworski, Taylor; Kimbrough, Erik O. (International economic review (Philadelphia), 2016)
In laboratory asset markets, subjects trade shares of a firm whose profits in a linked product market determine dividends. Treatments vary whether dividend information is revealed once per period or in real time and whether the firm is controlled by a profit-maximizing robot or human subject. The latter variation induces uncertainty about firm behavior, bridging the gap between laboratory and field markets. Our data replicate well-known features of laboratory asset markets (e.g., bubbles), suggesting these are robust to a market-based dividend process. Compared to a sample of previous experiments, both real-time information revelation and endogenous uncertainty impede the bubble-mitigating impact of experience.